DINÂMICA E PROJEÇÕES DA DISTRIBUIÇÃO DIAMÉTRICA EM FLORESTA OMBRÓFILA MISTA NA REGIÃO CENTRO-SUL DO PARANÁ - Monteiro, Fabio Gomes (2019)
The objective of this research was to evaluate a Mixed Ombrophilous Forest in relation to its phytosociology, dynamics (increment, recruitment and mortality) and test prognosis of diametric structure for the forest and for the three species with the highest Índice the Value of Importance (IVI). The research was conducted with data from permanent plots installed in the Irati National Forest (FLONA), Paraná State, Brazil using 25 permanent plots of one hectare. The six measurements of these plots took place every three years, from 2002 to 2017, completing 15 years of monitoring. Growth in diameter, recruitment and mortality were evaluated during this period for the forest and for the three species with higher IVI. Three projection methods were used: Transition Matrix, Movement Ratio and Wahlenberg Method. The accuracy of the projections generated was evaluated by the Kolmogorov-Smirnov adherence test (K-S) and Reynolds Index (IR). In the 2002 measurement, 14,287 individuals with a diameter at 1.3 m from the ground (DBH) greater than or equal to 10 cm were recorded. The three species that stood out for IVI in 2002 were Araucaria angustifolia, Ilex paraguariensis and Ocotea odorifera. I. paraguaensis was removed from ranking among the three, leaving Ocotea porosa in its place, leaving the first three species with timber potential. This species was withdrawn because it is mainly used for non-timber products, and also because projections are mainly used to predict growth in order to regulate the production of timber raw material. During the 15 years of monitoring, the forest presented an average diameter increment of 0.23 cm.year-1 and the number of dead trees was higher than the number of trees entered in some periods. For the evaluated periods, the largest number of stems is concentrated in the first two diameter classes, in the years 2002 and 2017, however, in 2017 the number of stems increased from class 25, compared to 2002. It was observed that in the analyzed periods there was a tendency of reduction in the projection of the total forest density for the three tested methods. The best projections for the forest in 2008 and 2011 considering the lowest Reynolds Index were the Transition Matrix and the Wahlenberg Method. Although mortality rates in some evaluation periods are higher than ingrowth, the forest gained 7.36 stmes.ha-1 over 15 years of monitoring. The Transition Matrix, Movement Rati and Wahlenberg Method, for a three-year interval were consistent in the prognosis of the diametric distribution only for projections until 2011. However, for the six-year interval, only the Transition Matrix was effective.The three methods were appropriate for the projections of A. angustifolia, O. odorifera and O. porosa, except the Movement Ratio method which did not show good projections for O. porosa. For six year interval projection the three methods were consistent to predict the number of A. angustifolia, O. odorifera and O. porosa stems.